Non-Anatomic Reconstruction in Multiligament Knee Injuries: A Functional Approach - Mihai Hurmuz; Cătălin-Adrian Miu; Daniel Ceachir; Romulus-Fabian Tatu; Mihai Andrei; Bogdan Andor; Alexandru Catalin Motofelea; Călin Tudor Hozan (Medicina)
Background/Objectives: Multiligament knee injuries, involving damage to multiple stabilizing structures, present a significant challenge in orthopedic surgery, often resulting in knee instability and compromised function. While anatomic ligament reconstruction has been traditionally advocated, non-anatomic techniques may provide effective alternatives, particularly for patients with moderate functional demands who do not require high-level athletic performance. Material and methods: In this study, we assessed the outcomes of a non-anatomic, hybrid surgical approach involving combined arthroscopic and open non-anatomic ligament reconstruction in 60 patients with multiligament knee injuries. Using simplified reconstruction methods for the medial collateral ligament (MCL) and lateral collateral ligament (LCL), we tailored the procedures to the needs of active, non-professional patients. Functional outcomes were evaluated using the International Knee Documentation Committee (IKDC) Questionnaire, Lysholm Knee Scoring Scale, and Knee Injury and Osteoarthritis Outcome Score (KOOS). Results: Postoperative improvements were significant, with the total IKDC score increasing from a median of 39.1 preoperatively to 75.9 postoperatively, Lysholm from 61.0 to 87.0, and KOOS from 47.6 to 85.7 (p < 0.01). The results demonstrated significant improvements across all scoring systems, with enhanced knee stability, reduced pain, and better quality of life. Conclusions: These findings support the feasibility of non-anatomic reconstructions as a practical solution for patients seeking a return to daily activities and recreational sports without the complexity of full anatomic reconstruction.